Economic Impact of Chemical Pesticide Ban on Mealybug Management in Commercial Banana Farms in Cameroon Highlights the Need for Policy Initiatives on Sustainable Alternatives - Henry Ikome Becke; Tange Denis Achiri; Justin Nambangia Okolle; Nelson Neba Ntonifor; Christopher Ngosong (International Journal of Agronomy)
Banana (Musa spp.) production is source of food, income and foreign exchange, but banana mealybug (Pseudococcus elisae) infestation is a major production constraint that was only highlighted in 2007 following rejection of banana from Cameroon Development Cooperation (CDC) in international markets. Increased banana rejection with the ban on chlorpyrifos insecticide-treated bags in 2019, requires insights on the current status of banana rejection and relevant policies. In order to advance evidence-based debates on policy implications of chlorpyrifos ban on banana trade, we explored secondary data from CDC at prechlorpyrifos ban (PreCB; 2014–2016) and postchlorpyrifos ban (PostCB; 2020–2022). Thereby, providing situational insights on impacts of mealybug infestation at CDC farms on market rejection of banana and financial losses in PreCB and PostCB. This will facilitate relevant policy formulations that can enable adaptation to current and future shocks on pesticide use and banana trade. Findings revealed no banana rejection due to mealybug infestation in at least 2 months of PreCB years, whereas banana was rejected in all 12 months of PostCB years. Rejection of banana bunches due to mealybug infestation increased by 6–folds in PostCB with the highest in February 2021 and January 2022. Monthly financial loss resulting from mealybug infestation differed significantly (p<0.029) between PreCB (∼US$3100) and PostCB (∼US$7600). Besides market rejection of banana and economic losses due to mealybug infestation, business rating and reputation of CDC are downgraded, highlighting the urgent need for policy initiatives to reduce dependence on chemical pesticides, and promote sustainable alternative management options.